2020
DOI: 10.1002/mrm.28211
|View full text |Cite
|
Sign up to set email alerts
|

A within‐coil optical prospective motion‐correction system for brain imaging at 7T

Abstract: Purpose: Motion artifact limits the clinical translation of high-field MR. We present an optical prospective motion correction system for 7 Tesla MRI using a custombuilt, within-coil camera to track an optical marker mounted on a subject. Methods: The camera was constructed to fit between the transmit-receive coils with direct line of sight to a forehead-mounted marker, improving upon prior mouthpiece work at 7 Tesla MRI. We validated the system by acquiring a 3D-IR-FSPGR on a phantom with deliberate motion ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…51 Even small movements or breathing will create artifacts in susceptibility sensitive techniques such as T 2 *-weighted sequences or echo planar imaging (EPI). 52 Several retrospective and prospective correction methods have been suggested, and although promising, tracking of optical markers 53 or NMR-active probes 54 can be challenging because of the tight space in standard head coils and require a workflow impractical for clinical use. Alternatively, methods based on embedding fat-selective navigators 55 or phase navigators 56 into sequence designs have been successfully used in a variety of applications.…”
Section: Motion Correctionmentioning
confidence: 99%
“…51 Even small movements or breathing will create artifacts in susceptibility sensitive techniques such as T 2 *-weighted sequences or echo planar imaging (EPI). 52 Several retrospective and prospective correction methods have been suggested, and although promising, tracking of optical markers 53 or NMR-active probes 54 can be challenging because of the tight space in standard head coils and require a workflow impractical for clinical use. Alternatively, methods based on embedding fat-selective navigators 55 or phase navigators 56 into sequence designs have been successfully used in a variety of applications.…”
Section: Motion Correctionmentioning
confidence: 99%
“…In addition, the usage of CAM can be applied to other (imaging) modalities as well, e.g., home care vital sign monitoring. 19 Several studies have been published on contact-free physiological monitoring, [32][33][34][35][36][37] but they did not focus on cardiac 4D flow MRI. Harder et al compared the same camera type and setup (abdominal imaging) to existing respiratory gating methods and reported that camera-based respiratory triggering (prospective gating) significantly improved image quality of 3D cholangiopancreatography images compared to conventional respiratory belt triggering.…”
Section: Discussionmentioning
confidence: 99%
“… 158 Also, novel coil designs with built-in camera to track an optical marker have been used to overcome subject motion during scanning. 159 …”
Section: New Horizons In Ultra-high-field Imagingmentioning
confidence: 99%